Degeneration of Dopaminergic Neurons Due to Metabolic Alterations and Parkinson’s Disease - Song, Juhyun; Kim, Jongpil (Frontiers in Aging Neuroscience, 2016)
The rates of metabolic diseases, such as type 2 diabetes mellitus (T2DM), obesity, and cardiovascular disease, markedly increase with age. In recent years, studies have reported an association between metabolic changes and various pathophysiological mechanisms in the central nervous system (CNS) in patients with metabolic diseases. Oxidative stress and hyperglycemia in metabolic diseases lead to adverse neurophysiological phenomena, including neuronal loss, synaptic dysfunction, and improper insulin signaling, resulting in Parkinson’s disease (PD). In addition, several lines of evidence suggest that alterations of CNS environments by metabolic changes influence the dopamine neuronal loss, eventually affecting the pathogenesis of PD. Thus, we reviewed recent findings relating to degeneration of dopaminergic neurons during metabolic diseases. We highlight the fact that using a metabolic approach to manipulate degeneration of dopaminergic neurons can serve as a therapeutic strategy to attenuate pathology of PD.